Apache devil - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 2023)
"Apache Devil" by Edgar Rice Burroughs is a novel written in the early 20th century. The story revolves around Apache culture and their struggles against white settlers, featuring the central character Shoz-Dijiji, also known as the "Apache Devil," who is a young war chief. His internal conflicts about love, loyalty, and the plight of his people serve as the backdrop for a dramatic tale set in the American Southwest. At the start of "Apache Devil," we are introduced to a vibrant Apache camp under the full moon, where traditional dances and rituals are in full swing to pray for rain. The narrative establishes the central tension between survival and the struggle against oppression as we see Shoz-Dijiji, a young war chief, grappling with feelings of love for a white girl he has rescued, which complicates his identity and his beliefs. As the political climate escalates, with whispers of Geronimo$1 (Bs anger and impending conflict, Shoz-Dijiji's friendship with Gian-nah-tah reveals themes of loyalty, pride, and the cost of war. The opening sets a rich, emotionally charged atmosphere as it intertwines personal and collective conflicts against the backdrop of a changing world. (This is an automatically generated summary.)s
Release date is 2023-02-21
Al Haines, Cindy Beyer & the online Distributed Proofreaders Canada team at http://www.pgdpcanada.net
Keywords: Western stories; Apache Indians -- Fiction